The Development of Tourism Products in Sangiran Tourism Village, Krikilan Village, Kalijambe District, Sragen - Mega Aldora; Lilis Jayanti; Jacob Ganef Pah; Eka Paramita Marsongko; Yanthi Adriani (Politeknik Negeri Bandung, 2022)
Sangiran Tourism Village or Krikilan Village is one of the tourist villages that has unique geology, being part of the Sangiran Cultural Conservation area which has been designated as a UNESCO World Cultural Heritage. Therefore, tourism development in Sangiran Tourism Village should not be carried out arbitrarily and planning is needed through the development of appropriate tourism products. This study uses a descriptive method and a qualitative approach to find out the actual situation and phenomena. The results obtained from this study are the actual conditions of tourism products in the Sangiran Tourism Village where tourism in the Sangiran Tourism Village currently only utilizes the actual attraction in the form of the Sangiran Ancient Human Museum. The potential possessed by the Sangiran Tourism Village is the natural potential in the form of geological conditions, landscapes, and rural life that are still maintained. Some of the suggestions made are the use of potential tourist attractions, the preparation of tour packages, and the preparation of a code of ethics for tourism development.